Futures Images of Good life for Urban Youth in Sri Lanka - Seneviratne, Nathali (My University, 2024)
The societal emphasis on pursuing a good life through materialistic values has resulted in complex challenges for humanity. Therefore, looking for alternative ways of living the good life which embrace the human and planetary well-being is a growing research topic in diverse disciplines. Contrary to the growing research interest, the youth futures and particularly the futures of youth in developing economies, has been given less attention in academia. This study actively inquiries into the larger question ‘‘ What are the alternative ways of living a good life that embrace both human and planetary wellbeing in ten years?’’. To respond to this primary goal of the study, the research aimed to create images of future of good life that empower youth futures in developing economies, focusing on Sri Lanka, while implicitly explore how the application of envisioning contributes to shape the youth futures. In addition, the study takes a particular interest in exploring the preferred lifestyle choices of Urban Youth in their future good life. The inquiry positioned within social constructionist and critical futures paradigms. The theoretical framework for the study was derived from combining the perspectives of the Global North and Global South on the good life. The study adapts envisioning approach, combining the mindful meditations and mental time travel exercise followed by a semi structured interview. The method was designed to facilitate young people to envision their preferred futures. Further, Causal Layered Analysis is utilised as the analysis method to deepen the futures and to explore the framing issues, in creating alternative ways of living the good life. The research produced several key findings. The study created four images of the preferred futures. First, ‘Back to Nature’, which illustrated a life that youth is having a reciprocal relationship with nature. Second, Shangri-.la, in this image , the good life is centered around the development of spirituality and equality. Third, ‘Wanderlust’, the good life built around personal growth, adventure, and openness to diversity. Finally, the Minimalistic Urban Heaven illustrated good life, that embraces minimalism, simplicity, balance and harmonious integration of technology into daily life. Furthermore, the envisioning process enabled participants to reach beyond the everyday cognition and create images of futures which are radical and novel. The main conclusion is divided in to three critical aspects. Upon reflecting on futures images, the study suggests, future of good life among urban youth in Sri Lanka, is intrinsically linked building resilience as the images illustrate how young people prefer to cope with the foreseen future challenges and creatively tackle prevailing issues in their own envisioned futures. From a theoretical stand point, the study draws the connection to the concept of good life by considering both Global North and Global South perspectives and further recommends need for integration of diverse disciplinary perspectives to understand future of good life holistically. From the methodological standpoint, the study provided space to explore future possibilities the urban youth aspire to have in future.
Keywords: Good life, young people, images of future, preferred futures, envisioning, Causal Layered Analysis.